Comparison of Voltage-Vector Control based on Duty Cycle Analysis in Three-Phase Four-Leg System Active Filter - Indriarto Yuniantoro; Rudy Setiabudy; Ridwan Gunawan (Institute of Advanced Engineering and Science, 2016)
Comparison of voltage vector control in various forms of tetrahedron that result from switching combination on three-phase four-leg system active filter is presented especially asymmetric tetrahedron shape which is a projection pqr-coordinate into αβ0-coordinate. Parameter tetrahedrons such as modulation boundary-line, reference vector, switching duration time and duty cycle are described. Duty cycle analysis conducted on the Shen’s model, the Zhang’s model, the Perales’s model and asymmetric’s model are presented. The characteristics results showed that switching combination of each IGBT conductor especially its reviews on the neutral wire. Asymmetric tetrahedron can be proposed as control technique in three-phase four-leg system active filter.